(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the effectiveness of a special dietary food product in improving the nutritional status of children with picky eating in Thai Nguyen province. Method: Children in the intervention group received 50g of Calokid Gold supplement twice a day (equivalent to 470 kcal/day and 20 micronutrients and minerals). Results: After 3 months of intervention, the weight and height gains in the intervention group at 1, 2, and 3 months were 0.37 kg, 0.79 kg, and 1.07 kg; 0.80 cm, 1.42 cm, and 2.02 cm), respectively - significantly higher compared to the control group (0.12 kg, 0.48 kg, and 0.69 kg) and (0.59 cm, 1.09 cm, and 1.61 cm), p < 0.001. Improvements in WAZ, HAZ, and WHZ were also significantly greater in the intervention group than in the control group (p < 0.001). The prevalence of wasting and risk of wasting in the intervention group was 18.9%, significantly lower than the control group at 27.5% (p < 0.05). Conclusion: Using nutritional products effectively increases weight, height, WAZ, WHZ, and HAZ indices, reduces malnutrition rates, and lowers the risk of wasting in picky eaters.